The Effects of Audio-Lingual Method on Children’s English Acquisition - Irna, Irna; Mahmud, Murni; Salija, Kisman (Har Press Indonesia, 2023)
The purpose of this study was to explore the effects of the audio-lingual method on children's English acquisition. This study used a qualitative method with a descriptive qualitative design. The subjects of this research are the children in Bone District who take an English course at the basic level. In this case, the researcher used Aura Lentera Fitrah, which is the English course, as the research setting. Besides, the researcher used purposive sampling to get the sample. To collect the data, this research used interviews as instrument. The result of this research showed that the effects of the audio-lingual method on children's English acquisition were engagement and fun; enhanced memorization and repetition; building teacher-student relationships; and listening and speaking opportunities. This research highlights the importance of the audio-lingual method technique for teaching listening and speaking skills to Indonesian EFL students. This method helps students acquire language through formation habits, adapting English phonemes, and improving pronunciation. It also enhances students' communicative competence and can be applied to non-formal institutions for teaching English as a co-curricular activity in Indonesia's current curriculum system.